Investigating the Role of the Cultivated Banana Value Chain as a Potential Source of Sustainable Income for Local Communities in Lao PDR - Wongpit, Piya; Inthakesone, Bounmy; Sisengnam, Keuangkham; Syphoxay, Pakaiphone (Research on World Agricultural Economy, 2023)
Cultivated bananas have gained attention due to the environmental and social impacts of Cavendish bananas in the northern part of Laos. This study investigated the value chain of cultivated bananas and its implications for sustainable income generation. Basic statistical analysis was used to assess the value added by cultivated bananas, while stakeholder analysis and value chain mapping were used to identify key actors and relationships. The determinant of commercialization is observed through the regression model and the impact of commercialization is investigated through the second stage regression. The study found that the banana value chain in Laos is driven by the export market. Farmers generate the highest profit, but they receive the lowest distribution of value-added. Banana commercialization can significantly increase the income of farmers, but the impact is not equal for all farmers. Bananas are a sustainable income source for households in Laos, and they have the potential to be promoted in high-value markets if the farmers create new products and improve skills of management, marketing, and finance with the support from government policies. ER